(untitled) (International Journal of Food and Nutritional Sciences, 2022)
For a number of reasons, it would be beneficial to lessen the Indian economy’s reliance on currency. India has one of the highest ratios of cash to GDP in the world, yet it costs money to lubricate the economy with paper. The Cost Of Cash In India, a 2014 Tufts University research, estimates that the Reserve Bank of India (RBI) and commercial banks spend roughly Rs21,000 crore per year on cash operations. A significant advantage in a nation with tight budgets is that moving away from cash will make it harder for tax evaders to conceal their income. The Government of India’s main initiative, the Digital India Programme, aims to make India into a knowledge-based society and economy. A variety of digital payment methods are offered in an effort to encourage cashless transactions and make India a society that uses less cash. These methods include Point of Sale, Internet Banking, Mobile Banking, Micro ATMs, Mobile Wallets, Bank Prepaid Cards, USSD, AEPS, and UPI. It takes time to transition from a cash-based economy to one that is cashless. India has begun to make its hesitant initial steps in the direction of this objective. Making India a digital economy is the aim. Without the support of the entire nation, this objective cannot be accomplished. To get the desired outcome, deliberate effort must be made on a regular basis. The Indian government has launched a number of measures to get the nation started in the digitization process. Bharat Interface for Money, or simply BHIM, is one among them. Some of the questions posed above are the focus of this investigation. The purpose of the study is to evaluate how well-informed individuals are about the BHIM app. The survey also aims to determine how users perceive the BHIM app. It will inadvertently show their viewpoint, ideas, and opinions on India turning cashless. Given that this is the present government’s top priority, it will aid in taking the necessary actions to bring about such a significant transformation. For the government to properly adopt and kickstart the digital economy, a mentality shift is now required. The research study will contribute by offering insightful recommendations for improving the most promising application. The study will assist in moving India closer to its goal of developing a digital economy.